Resultados clínicos e funcionais de pacientes submetidos à reconstrução cirúrgica minimamente invasiva para o tratamento das rupturas crônicas do tendão calcâneo. - Silveira, Juliana Doering Xavier Da [UNIFESP] (2019)
Introduction: Achilles tendon chronic ruptures most often need surgical treatment to achieve the best possible functional outcomes. The minimally invasive approach described in this study aims at establishing a reliable and robust construction with minimal skin and wound complication rates. Objective: the present primary transversal study aims to assess the functional and clinical results after undergoing minimally invasive surgical approach as measured by the Single Heel Rise Test, anthropometric measures and two validated scores. Method: thirteen patients who had undergone the described surgical treatment during the period encompassed between 2013 and 2017 were evaluated after a minimal 12-month post-operative period. All patients performed the Single Heel Rise Test to assess muscle endurance. Their calf circumference and weight-bearing ankle dorsiflexion angle were measured for this very purpose. The patients were additionally assessed with the Achilles Tendon Total Rupture Score and Visual Analogic Scale to determine subjective clinical results. Results: a complication rate of 15.4% (2 patients) was established. A difference between both legs for the dorsiflexion angle (p<0.05) and calf circumference measurement (p<0.05) was found. A variation of 36% of muscle endurance for the functional heel rise test (p<0.05) was also observed. ATRS score (mean 82.8) was high despite the muscle endurance measures. Conclusion: the limbs operated according to the purposed technique showed less resistance strength when compared to the non-operated side. No correlation was established between this finding and the test scores obtained from the assessment of the subjective functional results. As such the minimally invasive approach performed in the patients in this study has robustly demonstrated to provide both satisfaction and good functional results.